New Ampharetidae (Polychaeta) from the deep Southern Ocean and shallow Patagonian waters - Schüller, Myriam; Jirkov, Igor A. (Zootaxa, 2013)
The terebellomorph Ampharetidae are among the most speciose polychaete families in Southern Ocean waters, especially in the deep sea. Because specimens are very fragile and species are often only present in low abundances, identification of species is challenging. In the present study the Ampharetidae of the expeditions ANDEEP I–III to the deep Weddell Sea and adjacent basins and samples from Patagonia were identified. In 574 individuals over 40 different species were found, of which only 13 could be assigned to described species without doubt. At least ten new species were found in the material of which eight are described herein, one of them belonging to a new genus. These are Abderos minotaurus gen.nov. n.sp., Amage micropaleata n.sp., Anobothrus paleaodiscus n.sp., Anobothrus wilhelmi n.sp., Noanelia orensanzi n.sp., and Zatsepinia antarctica n.sp. from ANDEEP-samples, and Amage septemdecima n.sp. and Anobothrus rubropaleatus n.sp. from the Knipovich expedition to Patagonian waters. In addition, diagnoses of all respective genera are given, as well as a key to all Anobothrus species recognized world-wide.